Multi-modal argumentation and rhetoric in judicial proceedings. (2nd January 2020) - Novak, Marko
Abstract: Multi-modal argumentation is a relatively new approach in argumentation theory. In Gilbert's approach to multi-modality, it focusses not only on the logical mode of argumentation but also on the emotional, the kisceral, and the visceral: the so-called "alternate" modes. Due to the formal institutional constraints in law, the logical mode (in its dialectical variant) is a normative imperative due to the demands of the rule of law. However, especially in the so-called unclear cases, we can find traces of the alternate modes, either in their dialectical or rhetorical dimensions. If it already has been claimed that logic is only one part of legal "business, " a multi-modal argumentation analysis of law, in a Gilbertarian style, is presented here for the first time.